Comparing the effectiveness of treatment based on acceptance and commitment with and without self-compassion, conscious attention to the spiritual reactions of women with corona anxiety and insecure attachment to their spouses - Okati, Gholan Nabi; Shahabizadeh, Fatemeh; Bahrainian, Seyed Abdulmajid (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to compare the effectiveness of Acceptance and Commitment Therapy (ACT) with and without self-compassion mindfulness on the spiritual reactions of women with COVID-19 anxiety who have insecure attachment to their husbands, with a two-month follow-up period. Method: This clinical trial was conducted in 2021 on 48 female teachers in Zahedan. Women with COVID-19 anxiety and insecure attachment to their husbands were selected through purposive sampling and randomly divided into three groups: Intervention 1 (16 participants receiving ACT), Intervention 2 (16 participants receiving ACT with self-compassion mindfulness), and a control group (16 participants). The Coronavirus Anxiety Scale, Relationship Scales Questionnaire, Patience Scale, and the Spiritual Control Language Questionnaire were used, and data were analyzed using SPSS software version 26. Results: Results showed that ACT with and without self-compassion mindfulness, compared to the control group, significantly increased cognitive control of language and patience (P < 0.05). ACT combined with self-compassion mindfulness was more effective in improving cognitive control of language and patience than ACT alone, and this effect was maintained at follow-up. Conclusion: ACT combined with self-compassion mindfulness, as a sustainable intervention, can be used in health and treatment centers for women with COVID-19 anxiety who have insecure attachment to their husbands, to enhance cognitive control of language and patience.